Disseminated adenovirus infection twenty-five years post heart-lung transplant complicated by haemophagocytic lymphohistiocytosis - Vathenen, Ramu; Rokadiya, Sakib; Lambourne, Jonathan (Clinical infection in practice, 2021)
•Recognising atypical viral infections early is essential in susceptible patients.•Disseminated adenovirus infection may occur at any time in transplant patients.•Treatments for adenovirus are toxic and not readily accessible.•HLH should be considered in any critically ill patient, regardless of aetiology. Disseminated adenovirus infection is well recognised in transplant patients and carries a high mortality. Treatment options are limited and potentially hepatotoxic and nephrotoxic. Adenovirus is one of many known triggers for haemophagocytic lymphohistiocytosis (HLH), a life-threatening hyper-inflammatory response. We present a patient with disseminated adenovirus-driven HLH occurring 25 years after a heart-lung transplant, the longest documented in the literature. A 75-year-old man presented to the emergency department with a two week history of fever, cough and diarrhoea. Past medical history included heart-lung transplant. He was febrile and tachycardic but appeared well. Blood tests showed acute kidney injury, transaminitis and pancytopenia. Chest radiograph was unremarkable. Initial treatment was with co-amoxiclav and intravenous fluids. Computerised tomography of thorax and abdomen showed moderate splenomegaly. After 48 h, he remained febrile and hypotensive with worsening renal and hepatic function. Antibiotic therapy was broadened to meropenem and amikacin. Nasopharyngeal swabs returned positive for adenovirus PCR and subsequently, the preliminary diagnosis was adenovirus gastroenteritis with hypovolaemia. Blood cultures were negative with undetectable cytomegalovirus and Epstein-Barr Virus DNA in blood samples. On day 4 he developed fulminant multi-organ failure. HLH was suspected, given bone marrow and splenic involvement with laboratory investigations showing hyperferritinemia, hypertriglyceridemia and haemophagocytosis on bone marrow biopsy. Cidofovir/Brincidofovir were discussed as potential treatments but were difficult to obtain with concern regarding toxicity. Intravenous immunoglobulins were commenced for HLH on day 6. Adenovirus was later detected by PCR in urine, stool and blood samples. He continued to deteriorate and died on day 8. This case highlights the importance of considering a broad range of infectious aetiologies in all transplant recipients, even those on stable immune suppression. Immune senescence in an increasingly older transplant population may represent an additional risk factor to consider. Early diagnosis is crucial in such cases.